Second grade students’ english speaking skills in communicative language teaching lessons (2016)
This research study was carried out with students of second grade at the Mount Vernon school in Bogota Colombia. The main objective was to describe second grade students‟ English speaking skills performance during the implementation of lessons based on communicative language teaching. This study was based on principles of action research design and it used video recordings, students‟ interviews, and teacher‟s journals to collect data, as well as lessons to inform students‟ speaking skills by providing input activities that encourage their self- confidence and the ability to communicate using speaking skills. The purpose of this paper is to describe the pedagogical implementation that was implemented, and present the results and conclusions that were reached after analyzing the collected data. The data analysis indicate that students of second grade show, that the implementation of lessons plan allowed them use the speaking skills during the intervention in the English classes and the qualitative analysis support this view by showing that students felt more confidence towards the learning process